Jurnalisme Islam di Tengah Transformasi Jurnalistik Digital - Hakim, Lukman (Jurnal Komunikasi Islam, 2019)
This article discusses the concept of Islamic journalism as an alternative to negative journalistic practices as a result of media digitalization which is marked by the birth of the internet, such as the practice of "cloning journalism", journalistic practices that prioritize sensation rather than presenting the truth, and so forth. The phenomenon of digital transformation has forced the mass media, especially print media to provide digital versions of information of the most public’s increasing interest. This article believes that Islamic journalism enriches the Journalistic Code of Ethics, such as honesty, fairness, standing for the truth, and perseverance to innovate. Hence, Islamic journalism is able to be a new perspective and a solution in the midst of community uncertainty in sorting out correct and accountable information.